A nomogram for predicting stones recurrence in patients with bile duct stones undergoing laparoscopic common bile duct exploration. Issue 4 (22nd February 2022) - Xie, Wangcheng; Yang, Tingsong; Zhou, Xue; Ma, Zhilong; Yu, Weidi; Song, Guodong; Hu, Zhengyu; Gong, Jian; Wang, Yuxiang; Song, Zhenshun
Abstract: Background: The recurrence of bile duct stones is a long‐term outcome for patients undergoing laparoscopic common bile duct exploration (LCBDE) that is worthy of attention. This study aimed to investigate long‐term risk factors for stones recurrence after LCBDE and develop a nomogram for predicting the risk. Methods: The clinical data on consecutive patients with bile duct stones undergoing LCBDE at Shanghai Tenth People's Hospital between January 2014 and February 2019 with a follow‐up period longer than 2 years were reviewed. Independent risk factors of stones recurrence identified by the Cox regression model were used to develop a nomogram in predicting stones recurrence after LCBDE. Results: Eight hundred and twenty‐two patients were eventually included in this study. Of these patients, 42 (5.11%) developed stones recurrence. The cumulative incidences of stones recurrence at 1, 3, and 5 years after LCBDE were 1.34%, 4.36%, and 7.14%, respectively. Independent risk factors of stones recurrence were identified to be age (HR = 1.04, 95% CI = 1.02‐1.07), T‐tube drainage (HR = 3.28, 95% CI = 1.23‐8.72), fatty liver (HR = 2.69, 95% CI = 1.39‐5.20), urinary calculus (HR = 4.68, 95% CI = 2.29‐9.56), post‐cholecystectomy (HR = 5.21, 95% CI = 2.39‐11.33), and post‐ERCP + EST (HR = 2.87, 95% CI = 1.18‐6.96). By these factors, a developed nomogram showed a C‐index of 0.770 to predict stones recurrence. Conclusions: The nomogram, based on identified risk factors, showed good accuracy for predicting stones recurrence, which is valuable to guide these patients' follow‐up and prevention. Abstract : Stones recurrence rate for choledocholithiasis undergoing LCBDE is 5.11%. Six independent risk factors identified for stone recurrence include age, T‐tube drainage, fatty liver, urinary calculus, post‐cholecystectomy, and post‐ERCP + EST. The developed nomogram shows good accuracy for predicting stones recurrence, which is of potential value to guide doctors and remind patients to follow‐up.